(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This paper examines the relationship between the systems in Indian economy for insolvency related issues and its impact on economic development. Legal production is sufficiently high and overlapping laws have often decelerated the civil justice and increased the costs of the insolvency proceedings. For providing guarantee to creditors about safety of their business investment it is expected that bankrupts should be punished too quickly and severely. This can bring definite discouragement to entrepreneurs for taking financial risks and letting off defaulting debtors easily. Therefore, a certain degree of sophistication of the Bankruptcy Law is desirable at the least to guarantee creditors and make investments possible. This research paper provides an analysis of the development of Bankruptcy and Insolvency laws in India and its impact on net position of Non Performing Assets (NPA) of financial institutions in India. No country can be called as healthy economy without effective financial system. Present research paper focuses on insolvency laws existed in world economy as well as evolution of the regulatory framework and significant changes in regulations of the Insolvency and Bankruptcy Code 2016 (IBC).